Mapping of Migration Motivation from Digital Nomads in Bali - Daniel Susilo; Ida Ayu Laksmita Sari; Guellica Agnesia Claudia Thanos; Toong Hai Sam (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
The article examines digital nomadism with a focus toward migration elements utilising data analytics, bservation, and interviews. It looks at the reasons digital nomads moved to Bali, stressing important elements such as mobility, cost, lifestyle convenience, and culture. The study arranges and visualises these components to spot trends among the digital nomads. Results highlight the effects on global tourist marketing plans and migration policy, therefore providing information for academics, travel agents, and legislators. Through an analysis of digital nomads’ behaviour, expectations, and goals, this study helps to grasp better migration’s motivating factors and shapes informed migration policy. The findings above further help digital nomads by highlighting their specific motivation and preferences. The research additionally proposes strategies for promoting sustainability and maximising the benefits of tourism activities. This study provides a basis for understanding the impact of migration on atypical lifestyles.